1995
DOI: 10.1111/j.1440-1827.1995.tb03397.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and immunohistochemical findings in a case of mucinous cholangiocarcinoma

Abstract: A case of mucinous cholangiocarcinoma is reported. The patient was a 49 year old woman with the complaint of lumbago. Imaging examination disclosed a tumor 3.5 cm in diameter in the right hepatic lobe, which showed low density on computerized tomography scans and low signal intensity on T1-weighted magnetic resonance imaging (MRI) and high intensity on T2-weighted MRI. The hepatic tumor expanded rapidly and multiple pulmonary metastases and peritoneal dissemination developed. The patient died due to respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…As mentioned earlier, nine of 10 patients in whom the pathological stage was disclosed were found to have advanced disease with lymph node and/or distant metastasis, and 5‐year survival was achieved only in one microinvasive case. Sasaki et al 7. described the characteristics of mucinous cholangiocarcinoma as rapid growth, widespread metastases, and poor prognosis, in comparison to the characteristics of IPNB.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, nine of 10 patients in whom the pathological stage was disclosed were found to have advanced disease with lymph node and/or distant metastasis, and 5‐year survival was achieved only in one microinvasive case. Sasaki et al 7. described the characteristics of mucinous cholangiocarcinoma as rapid growth, widespread metastases, and poor prognosis, in comparison to the characteristics of IPNB.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, rapid growth of mucinous cholangiocarcinoma has been reported. 16,17 Ishida et al 18 reported a case of mucin-producing intrahepatic cholangiocarcinoma associated with bile duct-gastric fistula. But the patient presented with obstructive jaundice due to a large amount of mucin.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 In conclusion, by performing curative left hepatectomy with common bile duct resection and right hepaticojejunostomy for a mucin-producing cholangiocarcinoma, disease-free survival of 111 months was achieved. Further analyses need to be done to confirm the correlations of the expression of MUC-2 mucinantigen with a favorable prognosis.…”
Section: Discussionmentioning
confidence: 88%
“…[9][10][11][12][13] In accordance with these reports, the tumor from our patient was totally negative for MUC-1 and partially positive for MUC-2, and he has survived long-term without any sign of recurrence. On the other hand, Sasaki et al 14 reported a case of mucinous cholangiocarcinoma expressing MUC-1 mucin, with clinical features of rapidly expanding, widespread metastasis, and poor prognosis. Further careful immunohistochemical analyses of resected specimens from many more cases of mucinproducing cholangiocarcinoma would help to clarify the correlations between immunohistochemical characteristics and prognosis.…”
Section: Discussionmentioning
confidence: 99%